An ant colony system for solving fuzzy flow shop scheduling problem - Pour, Nasser Shahsavari; Ashkezari, Mohammad hossein Abolhasani; Andargoli, Hamed Mohammadi (International Journal of Engineering and Technology, 2012)
During the past years, the flow shop has been regarded by many researchers and some extensive investigations have been done on this respect. Flow Shop includes n works performed on m machines in a same sequence. It is very difficult in the real world to determine the exact process time of an operation on a machine. Therefore, we consider in this article the process time as trapezoidal fuzzy numbers. Our purpose is that we obtain a sequence of works using such fuzzy numbers in order to minimize maximum fuzzy time of completion entire jobs or fuzzy makespan. We offered an optimization algorithm of Ant Colony System (ACS) to solve this problem. Finally, we present computational results for explanation and comparison with other articles in future.